Fuse binding protein antagonizes the transcription activity of tumor suppressor protein p53 - Dixit, Updesh (BMC Cancer, 2014)
BACKGROUND: FUSE binding protein1 (FBP1) is a transactivator of transcription of human c-myc proto-oncogene and expressed mainly in undifferentiated cells. It is also present in differentiated normal cells albeit with very low background. FBP1 is abundantly expressed in the majority of hepatocellular carcinoma tumors and has been implicated in tumor development. Although it down-regulates the expression of proapoptotic p21 protein, it is not known whether FBP1 also interacts and antagonizes the function of tumor suppressor protein p53. METHODS: Western blotting was carried out to detect the expression level of FBP1, p21 and p53, and also p53 regulatory factors, BCCIP and TCTP; real-time quantitative PCR was done to determine the fold change in mRNA levels of target proteins; immunoprecipitation was carried out to determine the interaction of FBP1 with p53, BCCIP and TCTP. Cells stably knockdown for either FBP1; p53 or BCCIP were examined for p53 reporter activity under normal and radiation-induced stress. RESULTS: FBP1 physically interacted with p53, impairing its transcription activity and reducing p53-mediated sensitivity to cellular stress. Knockdown of FBP1 expression activated p53-mediated response to cellular stress while transient expression of FBP1 in FBP-knockdown cells restored the inhibition of p53 activity. FBP1 not only interacted with both BCCIP and TCTP, which, respectively, function as positive and negative regulators of p53, but also regulated their expression under cellular stress. In FBP knockdown cells, TCTP expression was down-regulated under radiation-induced stress whereas expression of BCCIP and p21 were significantly up-regulated suggesting FBP1 as a potential regulator of these proteins. We hypothesize that the FBP1-mediated suppression of p53 activity may occur via preventing the interaction of p53 with BCCIP as well as by FBP1-mediated regulation of p53 regulatory proteins, TCTP and BCCIP. Since FBP1 suppresses p53 activity and is overexpressed in most HCC tumors, it may have a possible role in tumorigenesis. CONCLUSION: FBP1 physically interacts with p53, functions as a regulator of p53-regulatory proteins (TCTP and BCCIP), and suppresses p53 transactivation activity under radiation-induced cellular stress. Since it is abundantly expressed in most HCC tumors, it may have implication in tumorigenesis and thus may be a possible target for drug development.